O-15 Volunteer befriending services: lessons from a randomised controlled trial on who accesses these services and how to maximise service impact. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Walshe, Catherine; Dodd, Steven; Algorta, Guillermo Perez; Hill, Matthew; Ockenden, Nick; Payne, Sheila; Preston, Nancy
Abstract : Background: Volunteer provided befriending or good neighbour services are an increasingly common element of hospice provision. However little is known about who accesses such services, nor their impact. The ELSA study is a large trial of volunteer befriending services across England, with an aim of evaluating the effectiveness of receiving care. Aim: To report data on who was referred to and used the befriending services provided as part of this trial. Methods: A wait-list controlled trial (ELSA) with nested qualitative case studies, with patients randomly allocated to intervention (immediate receipt of volunteering intervention) or wait list arm (four week wait for intervention). Patients (estimated to be in their last year of life) referred to volunteer befriending services across 11 end of life care providers in England. Trial data were collected at baseline, 4, 8 (12) weeks to explore quality of life as our primary outcome, with loneliness and social support as secondary outcomes. Baseline data were collected on personal characteristics and social networks. Trial registered: ISRCTN 12929812 Results: Service referrals (n = 369) resulted in 195 people entering the study. Patients mean age 72 years, 61% female, 84% retired, 58% living alone, 90% white ethnicity, 50% with cancer. No significant differences on quality of life at baseline were observed between genders, but as age increases, scores on social, psychological and environmental sub scales worsen ( ps . < 0.01). Age and living alone were significant predictors of lower environment scores ( ps . < 0.01). Quality of life scores were lower than those of comparator populations. Conclusion: This study is the first to examine volunteer befriending in a trial context, and describe the characteristics of those receiving care. Services appear appropriately targeted to vulnerable older adults who live alone, and potentially accessed by a wider range of people than other hospice services. Funded by the UK Cabinet Office. See also poster presentation #205.